The Kurdish great Chest Sheikh Ali Xan Zanaga (1610-1689) - Tawfiq, Ali T. (Humanities Journal of University of Zakho, 2018)
The renowned Kurdish personage, Sheikh Alikhan Zangene (1610 - 1688), held the highest governmental position during the Safavid period: Chancellor and Grand Vizier. His ministry and administration ruled for the lengthiest period in the history of the Safavid Dynasty. As such, he became ‘Sadrazam’ in the time when Safai Shah II was in power (1666 - 1694). Safi Shah II was the weakest of all Safavid rulers; much of his time was spent in harem houses among female concubine servants. He did not have any political education and not aware of how to rule. Because of his lifestyle and growing problem of excessive drunkenness, he did not intervene in state business. The power to govern the country was therefore in the hands of Sheikh Alikhan. Sheikh Alikhan improved governance in the country by reforming the economy, administration, military and political affairs. His 20 years as the Sadrazam and Governor, is marked as the most peaceful time in the history of the Safavid Dynasty. He wasn’t under the influence of Europeans and never embarked upon a war against the Ottomans, even though the Ottoman Empire was quite weak at the time. His main concern was reformation, prosperity and rebuilding the country. He created many buildings and institutions, including a number of Karwansaray, schools, bridges, checkpoints on roads, public baths and mosques, the overwhelming majority of which are still named after him as Khan or Sheikh Alikhan to this very day. Now Sheikh Alikhan is known and recognized as one of the most influential Sadrazam in the history of Iran.